1998
DOI: 10.1038/sj.bjp.0701665
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of P2Y receptor subtypes on haematopoietic cells

Abstract: 1 RT ± PCR-southern hybridization analyses with radiolabelled P2Y receptor cDNAs as probes indicated that the peripheral blood leukocytes and the human umbilical vein endothelial cells express P2Y 1 , P2Y 2 , P2Y 4 and P2Y 6 receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
103
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(110 citation statements)
references
References 44 publications
(60 reference statements)
6
103
0
1
Order By: Relevance
“…Here we found that these leukotriene antagonists also inhibit the effects of nucleotides acting at P2Y receptors in dU937 cells, which are known to express a number of nucleotide receptors, such as P2Y 2 or P2Y 4 [30]. In an effort to characterize the P2 receptor subtypes subject to negative modulation by CysLT 1 receptor antagonists we studied the interactions of these compounds in human P2Y 1 6 receptor were grown at 37 °C in a humidified incubator with 5% CO 2 /95% air in Dulbecco's modified Eagle's medium (JRH Biosciences, Inc., Lenexa, KS, USA) and F12 (1:1) supplemented with 10% FBS, 100 units/ml penicillin, 100 μg/ml streptomycin and 2 mM Lglutamine.…”
Section: Introductionmentioning
confidence: 67%
“…Here we found that these leukotriene antagonists also inhibit the effects of nucleotides acting at P2Y receptors in dU937 cells, which are known to express a number of nucleotide receptors, such as P2Y 2 or P2Y 4 [30]. In an effort to characterize the P2 receptor subtypes subject to negative modulation by CysLT 1 receptor antagonists we studied the interactions of these compounds in human P2Y 1 6 receptor were grown at 37 °C in a humidified incubator with 5% CO 2 /95% air in Dulbecco's modified Eagle's medium (JRH Biosciences, Inc., Lenexa, KS, USA) and F12 (1:1) supplemented with 10% FBS, 100 units/ml penicillin, 100 μg/ml streptomycin and 2 mM Lglutamine.…”
Section: Introductionmentioning
confidence: 67%
“…Previous studies by us and others have reported the presence of P2Y 6 transcripts in human spleen, placenta, thymus, small intestine, and leukocytes (neutrophils, lymphocytes, and monocytes) suggesting that P2Y 6 plays a role in immune defenses (7,10). However, the physiological responses mediated by UDP and P2Y 6 are not known.…”
mentioning
confidence: 86%
“…P2 receptors are divided into two subfamilies: the G-protein-coupled receptors (P2Y 1,2,4,6,[11][12][13][14] ) and the ligand-gated ion channels (P2X 1-7 ). The P2Y subtypes differ in their selectivity toward adenine (ATP, ADP) and uracil nucleotides (UTP, UDP) while all P2X receptors are activated by ATP [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The P2Y subtypes differ in their selectivity toward adenine (ATP, ADP) and uracil nucleotides (UTP, UDP) while all P2X receptors are activated by ATP [10,11]. Human primary monocytes and monocytic cell lines (THP-1 and U937) express the mRNA of various P2 receptors of which P2X 1,7 and P2Y 2,6,11 are common to all these cells [12,13]. There is growing evidence indicating that P2 receptors mediate some important proinflammatory responses activated by the stimulation of monocytes/macrophages with PAMP.…”
Section: Introductionmentioning
confidence: 99%